A study on the preferred sensory modalities for learning among children with Autism Spectrum Disorder (ASD) - Hassan, Mohammad Mujaheed; Hassan, Muhamad Hafiz; Isa, Badrul; Wardi, Rainal Hidayat; Michael, Valerie; Abdullah, Mohammad; Silah, Sumardianshah (Telematique, 2024)
Quality education is one of the Sustainable Development Goals (SDG) declared by the United Nations in September 2015. Criterion number four emphasises ensuring inclusive and equitable quality education and encouraging opportunities for lifelong learning. To ensure that children with exceptional needs, such as Autism Spectrum Disorder (ASD), enjoy equitable educational opportunities in academics and personality, "Parallel Education" was developed. Regardless of their origin or circumstances, all children should have access to high-quality education, according to the Sustainable Development Goals (SDGs). Autism is a complex developmental condition that affects people of all racial, cultural, and social backgrounds, regardless of their socioeconomic standing, way of life, or degree of education. To improve their brain growth and create teaching and learning materials, the criteria must be determined. It is crucially important and demands the specific attention of every designer for all the instructors to approach the needs of autistic children. Besides, conduct, social skills, and communication abilities are three crucial areas on which autism spectrum disorder has a considerable effect. This study primarily serves as a reference for the educational tools designers who seek to improve the emotional state of autistic children through the cognitive and affective domains, while also fulfilling their sensory modalities and helping their psychomotor development. The study also identified unique challenges and needs for autistic children who have sensory issues by focusing on an emotional evaluation.